An Efficient 5G Data Plan Approach Based on Partially Distributed Mobility Architecture; Sensors; Vol. 22, iss. 1 - Mohammad A. Sh. Al Shinwan; Laith A. Abualigah; Trong-Dinh H. Huy; Maryam A. Altalhi; Chulsoo K. Kim; Shaker E. El-Sappagh; Mokhamed Elsaed (Mohamed Abd Elaziz) A. M. Akhmed Mokhamed; Kyung S. K. Sup Kwak (2022, 2022)
Title screen